Evaluating the Predictive Potential of Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratios in the Second-Trimester Preterm Premature Rupture of Membranes (PPROM): A Retrospective Case-Control Study - Pınar Tuğçe Özer; Mehmet Özer; Süleyman Cemil Oğlak; Adnan Budak; Abdurrahman Hamdi İnan; Gökhan Tosun; Emrah Töz; Emine Zeynep Yılmaz; Varol Gülseren; Gökhan Bolluk; Mehmet Özeren (IMR Press, 2024)
Background: Proteolytic enzymes and specific cytokines have been associated with the underlying mechanism of preterm premature rupture of membranes (PPROM), contributing to weakened amniotic membranes. This study aims to elucidate the predictive role of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) during the early stages of PPROM, given the limited existing literature exploring this relationship in second-trimester cases. Methods: This retrospective case-control study was performed from June 2018 to June 2023. We included 159 pregnant women diagnosed with mid-trimester PPROM and 573 pregnant women who gave birth at term. We obtained complete blood cell counts in all patients. We used a receiver operating characteristic (ROC) curve to evaluate the cut-off, sensitivity, and specificity values. Results: Complete blood count evaluations revealed that in the mid-trimester PPROM group, neutrophil count, leukocyte count, hemoglobin (Hb) levels, NLR, and PLR were notably higher than those delivering after the 37th gestational week. These observations were identified not only in the first-trimester but also within 24 hours after membrane rupture. Contrary to prior research and to conventional patterns, our study identified a diminished mid-trimester NLR in cases of PPROM compared to the control group. Conclusions: In our study, we identified significant differences in lymphocyte counts, platelet levels, NLR, and PLR values between the PPROM group and the control group. Our study suggests that the NLR and PLR values from the first-trimester might be powerful indicators of PPROM risk.